Docência na educação profissional e tecnológica: conhecimentos, práticas e desafios de professores de cursos técnicos na Rede Federal - Geralda Aparecida de Carvalho Pena (2014)
This thesis analyzes the teaching in the Vocational-Technical Education, considering the teaching specificities in high school level courses and the technical subjects teachers profiles in the federal education system. These teachers are mostly professionals who have bachelor and post-graduate degrees (masters and doctorates) in their areas of expertise, but do not have specific teacher training. The main objective of this study is to identify and analyze the didactization strategies and the pedagogic content knowledge in the teaching practice of technical subject teachers and the teaching challenges in the Vocational-Technical Education, in the context of the Federal Institute of Technology, Science and Education. The survey was conducted through a case study with teachers from the various technical courses of the Federal Institute of Minas Gerais (Instituto Federal de Minas Gerais - IFMG) in the Ouro Preto campus, using varied instruments to collect data, such as document analysis, questionnaires, classroom observation and interviews. The analyses were based on the theoretical framework of the knowledge base for teaching (Shulman, 2005a, 2005b), on the didactic transposition (Chevallard, 1991), and on the Vocational-Technical teaching practice (Machado, 2008, Oliveira, 2010, 2013, Kuenzer, 2010), among others. The results point to the teaching specificities in the Vocational-Technical education and the teaching of its technical subjects. It was found that in the absence of a formal teacher training, teachers based themselves on different references in order to develop their teaching practice. As a teaching source of knowledge for technical subjects, the teachers experiences were prominent, both in the academic studies through post-graduate courses and in the professional career as engineers or teachers. In these spheres, knowledge and experience articulated to the teachers personal characteristics, to their perception of technical education and to the schools identity provided subsidies for the development of education through different strategies of didactization and for the confrontation of the challenges in the teaching practice. The data also showed that the new demands of the Federal Institutes have been creating tensions and anxieties concerning the relationship between teaching and research, as well as regarding the possibility of devaluation of technical education in all learning activities in the school. The survey results point to the need to recognize the uniqueness of the teaching in the Vocational-Technical Education and to a wider understanding of teacher training for this type of education. They point to the need for deep content knowledge to teach technical subjects and reinforce the importance of pedagogical training for teachers, since it is understood that this, articulated to the other elements of the educational process, can contribute to the minimization of the many challenges in the teaching practice. Furthermore, the study indicates the relevance of a state policy for teacher training in this type of education, as well as the in-service teacher training programs, which should be based on the thinking of the teaching practice, aiming to contribute to the professionalization of the Vocational Technical teachers in Brazil.